"Economic Policies Are the Best Social Policies": West German Neoliberalism and the Housing Question After 1945. (11th January 2018) - Haderer, Margaret
Abstract: This article challenges the widespread view that neoliberalism had become hegemonic in the late 20 th century by zooming into a less well‐known variant of neoliberalism, German ordoliberalism, whose political ascendency dates back to the 1940s and 1950s. Through the lens of post‐WWII housing policies—a central field of political intervention after 1945—this article focuses on the remaking of social policies as neoliberal policies in West Germany, a remake that rendered the market economy a key source of political legitimacy of the newly emerging, liberal democracy.